2017
DOI: 10.1177/1758998317698099
|View full text |Cite
|
Sign up to set email alerts
|

Therapy management of thumb carpometacarpal osteoarthritis: Exploring UK therapists’ perceptions of joint instability

Abstract: Introduction: Carpometacarpal joint osteoarthritis is a common and painful condition associated with ligament laxity, subluxation and joint instability. Therapy management includes several interventions targeting the symptoms associated with instability and subluxation. This study aimed to explore the perceptions of experienced therapists, about their understanding of joint instability in carpometacarpal joint osteoarthritis and its relationship with laxity, subluxation and strength, and the perceived effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…A study by Grant 11 described the wide variety of interventions but did not explore the approach to management by therapists. Our findings resonate with Jansen et al, 9 who highlighted the importance of a ‘package of care’ in treating thumb CMCJ OA. Clinicians also described how the steroid injection should be delivered as part of a package of care and not in isolation.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…A study by Grant 11 described the wide variety of interventions but did not explore the approach to management by therapists. Our findings resonate with Jansen et al, 9 who highlighted the importance of a ‘package of care’ in treating thumb CMCJ OA. Clinicians also described how the steroid injection should be delivered as part of a package of care and not in isolation.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies indicate the necessity of well controlled pain levels to enable or start exercises in this patient population. 9 This is consistent with what we identified that earlier use of steroid injections would help people engage with exercises better by relieving the pain. Surgery being seen as a ‘last resort’ resonates with the BSSH guidance: 20 Moreover, it reflects the ladder approach with surgery being the most invasive option with risks and complications.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations